Collaborative Mobile Learning with Smartphones in Higher Education - Zhampeissova, Korlan; Kosareva, Irina; Borisova, Uliana (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The advantages of mobile learning and the possibility of universal access to educational materials have a downside in the form of a possible lack of communication between the student, his/her teachers, and course mates. In this context, collaborative teaching methods can be applied to support learners in solving educational challenges. The objective of this work was to analyze the effectiveness of collaborative approaches in mobile learning. The research methods included two stages: an experiment on the introduction of collaborative mobile learning into the educational process and an online sociological survey. The use of the questionnaire method resulted from the need to collect quantitative data and analyze the effectiveness of training by determining the shares of respondents with positive and negative opinions toward m-learning. The examination was conducted in 2020 among 190 undergraduate sociology students studying at three universities of the Russian Federation (Moscow State Pedagogical University, M.K. Ammosov North-Eastern Federal University, and Tyumen State University), as well as among 76 undergraduate students of the direction "Education" studying at Abai Kazakh National Pedagogical University. The main practical result of this experiment was the introduction of mobile technologies in the previously used e-learning models and learning management systems of the considered educational institutions. The collaborative mobile environment was based on the principles of communication and cooperation of users, mutual learning, and teacher coordination of students' actions. The study confirmed that collaborative mobile learning could be flexibly transited from blended to distance learning models and vice versa. The analysis of the survey outcomes proved the validity of eight proposed hypotheses, both in terms of mobile learning impact on the quality of education and the influence of the collaborative environment on the development of students' competencies. The practical significance of research findings is in the fact that they allow the effective implementation of collaborative mobile learning technologies to form students' professional competencies.